Bioherbicidal Effects of Essential Oils Isolated from Thymus fallax F., Mentha dumetorum Schult. and Origanum vulgare L. - Yilar, M.; Bayan, Y.; Aksit, H.; Onaran, A.; Kadioglu, I.; Yanar, Y. (Asian Journal of Chemistry, 2013)
The chemical composition of essential oil isolated by hydrodistillation from the ground part of Mentha dumetorum Schult. collected from Tokat province in 2010 and Thymus fallax Fisch. & Mey. and Origanum vulgare L. collected from Ordu province in 2009 The main components of Thymus fallax were thymol (41.48 %), o-cymene (26.75 %), z-terpinen (15.84 %), terpinoline (2.11 %) that of Origanum vulgare were thymol (50.41 %), carvacrol (12.96 %), 2-bornene (11.28 %), z-terpinen (8.80 %), o-cymene (6.68 %) and that of Mentha dumetorum were carvone (39.64 %), eucalyptol (14.34 %), dihydrocarvone (12.78 %), limonene (7.79 %). To determine herbicidal activities of the essential oils two layers of filter paper were placed petri dish (6 cm diameter) then seeds of Avena sterilis L., Datura strumarium L., Cucumis sativus L. and Lactuca sativa L. were homogeneously distributed on filter paper. Filter papers were thoroughly moistened using distilled water. Piece of filter paper was glued inner parts of each petri dish's lid. Four different concentrations (0, 3, 5 and 7 μL/petri dish) of the essential oil were applied to the filter paper pieces. Then lid of each petri dish was closed immediately and sealed with parafilm. Petri dishes were incubated at 12 h dark-12 h light periods with an average temperature of 24 ºC for 7 days. All of the essential oils tested inhibited seeds germination, roots and shoots growths of A. sterilis, L. sativa, D. strumarium, C. sativus. Consequently, it was determined that essential oils of the plants had bioherbicid effects on seed germination and growths of some crops and weeds, but more detailed studies should be done under field conditions.